Rekonstruksi Pembelajaran untuk Mengatasi Kesulitan Belajar Alquran Hadis di Madrasah Ibtidaiyah Muhammadiyah pada Masa Covid-19 - Nita Kurniawati (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2021)
The implementation of this research is by using a qualitative approach, data is collected using observations, interviews and documentation studies. The results of the first study of al-Qur’an Hadits before the Covid 19 pandemic in Madrasah Ibtidaiyah Teluk Kuantan took place well and in accordance with the planned learning objectives. Second, the learning of the al-Qur’an Hadits at Madrasah Ibtidaiyah Muhammadiyah Teluk Kuantan when the pandemic took place made the situation and conditions of the learning process in the madrassa changed completely. This is because it is a government policy that prohibits schools from doing face-to-face learning processes, so that learners can only learn from home and teachers provide material online. Third, the learning of the al-Qur’an Hadits that had initially run smoothly turned out to change drastically with the covid-19 pandemic. Therefore, the reconstruction of the learning of the al-Qur’an Hadits becomes one of the alternatives so that how the learning materials that must be studied and tested by these learners can still be conveyed properly. Although the implementation of reconstruction of al-Qur’an Hadits learning is not fully running smoothly in Madrasah Ibtidaiyah Muhammadiyah Teluk Kuantan, but at least teachers have been able to plan and readjust the changes felt due to the pandemic.